Effect of Different Stocking Densities on Survival and Growth of Pomfret (Colossoma macropomum) - Mohd Husaini Alputra; Putriningtiyas, Andika; Isma, Muhammad Fauzan (Fakultas Pertanian Universitas Samudra, 2022)
Freshwater pomfret (Colossoma macropomum) is one of the fishery commodities with high economic value. This encourages the supply of pomfret for consumption to increase, so that the supply of seeds for rearing is also increasing. The purpose of this study was to determine the growth and survival of pomfret fry. The test fish used were Freshwater Pomfret with an initial length of 3 -5 cm with an initial weight of 2.1 - 2.5 grams, which were kept in a 30 liter container. The research method used is an experimental method using a completely randomized design (CRD), consisting of 5 levels of treatment with 3 replications. The results showed that treatment A (stocking density 50 birds/25 liters) showed the highest growth of 4.01 grams, with a length of 5.67cm, survival of 96.67%, and FCR of 6.98 The lowest growth was in treatment P1 ( stocking density of 10 fish/25 liters) was 2.97 grams, with a length of 4.31 cm, survival of 96.67% and FCR of 1.45. The results of observations of water quality measured during the study were still within the tolerance limits for the growth and development of Freshwater Pomfret. From the results of the research conducted, it is known that the best stocking density for growth and survival in the maintenance of Freshwater Pomfret is P5 treatment (stocking density of 50 fish/25 liters) with an average absolute weight of 4.01 grams, a growth rate of 0.100 grams/day. absolute length 5.67 cm. 100% survival.